Addressing Police Occupational Safety During an Opioid Crisis: The Syringe Threat and Injury Correlates (STIC) Score - Beletsky, Leo (J Occup Environ Med, 2020)
OBJECTIVE: To develop and validate Syringe Threat and Injury Correlates (STIC) score to measure police vulnerability to NSI. METHODS: Tijuana police officers (N=1,788) received NSI training (2015-2016). STIC score incorporates five self-reported behaviors: syringe confiscation, transportation, breaking, discarding, and arrest for syringe possession. Multivariable logistic regression was used to evaluate the association between STIC score and recent NSI. RESULTS: Twenty-three (1.5%) officers reported NSI; higher among females than males (3.8% vs. 1.2%; p=0.007). STIC variables had high internal consistency, a distribution of 4.0, a mode of 1.0, a mean (sd) of 2.0 (0.8), and a median (IQR) of 2.0 (1.2-2.6). STIC was associated with recent NSI; odds of NSI being 2.4 times higher for each point increase (p-value<0.0001). CONCLUSIONS: STIC score is a novel tool for assessing NSI risk and prevention program success among police.